ANALYSIS OF 1994 CURRICULUM , KBK, KTSP , AND 2013 STAIP CURRICULUM (PATI ISLAMIC HIGH SCHOOL) - Achmad Mishbakh Setia Ajii; Muhammad Khoirun Ni'am; Desti Rahmadani; Heny Kusmawati (Jurnal Scientia, 2023)
In an education there will be something called curriculum, because the nature of the curriculum is part of the systematics of education or can usually be used as a backbone in explaining material to achieve an educational success. From that, to achieve the right goals and also succeed, the curriculum must be able to develop according to the times. As from the 1994 Curriculum to the Competency-Based Curriculum (KBK), from KBK to KTSP, and from KTSP to the 2013 Curriculum until now, only a few schools have implemented what is called the Independent Curriculum. Changes to the Curriculum itself are usually influenced by several factors. from human needs that are always changing or usually can also be caused by economic, political, and also cultural factors.